Practical norms in emerging infectious disease control: lessons for transnational collaboration from a suspected newly emerging zoonosis outbreak in Ghana - James Wood; Andrew A Cunningham; Freya L Jephcott; Joseph Humphrey Kofi Bonney; Kennedy Owusu Arhin-Sam; Stephen Nyarko-Ameyaw; Paul Wenzel Geissler (BMJ Global Health)
Concern around the emergence of zoonoses with pandemic potential has fuelled significant foreign engagement with domestic infectious disease surveillance and response systems across Africa. These international efforts at augmentation have likely been hampered, however, by an inattention to how such systems actually manifest on the ground and the critical activities and undertakings that take place outside of official structures and protocols. Such deviations from official protocols have previously been treated as inherently detrimental to public service delivery. A growing body of anthropological scholarship arising out of west and east Africa, however, has revealed that such deviations are often crucial to realising some core function or facet of it. Further, these apparent acts of discretion can represent broadly standardised sets of practices and structures that can be elucidated through interviews and observation.In this paper, we present an ethnographic account of the investigations into a suspected outbreak of a newly emerging zoonosis in the Brong Ahafo Region of Ghana between 2010 and 2016. By following the unfolding of the responses to the Brong Ahafo Region outbreak and drawing on observations from contemporaneous zoonotic outbreaks in West Africa, we elucidate the kinds of unofficial professional practices and shared visions of public service delivery which shape, and frequently augment, national responses to suspected newly emerging infectious diseases. The paper advances recent anthropological work on practical norms by applying them to emerging infectious disease control systems and considering the role of professional ethos in coordinating their use. The paper also clarifies the nature and utility of such unofficial activities for foreign would-be reformers of domestic surveillance and response systems in Africa, potentially enabling more effective transnational engagement with, and strengthening of, these critical systems for emerging infectious disease control.